Genotype-dependent resilience mediated by melatonin in sweet corn - Tahoora Batool Zargar; Mawia Sobh; Oqba Basal; Szilvia Veres (BMC Plant Biology)
Abstract Background Water deficits, exacerbated by climate change and unpredictable weather, have become a significant global challenge to agricultural productivity. In this context, exogenous melatonin treatment is well documented as a stress alleviator; however, its effects on various biological processes, particularly in less-explored genotypes, remain understudied. This study aimed to enhance water deficit resilience in sweet corn by applying foliar melatonin to four genotypes-Messenger, Dessert, Royalty, and Tyson under two levels of water deprivation induced by polyethylene glycol at 8% and 12% concentrations in a hydroponic, controlled environment. Results The melatonin treatments were assessed for their impact on various morphological, physiological, and biochemical parameters under both normal and water-deficit conditions. Under severe water deprivation (12% PEG), melatonin increased root length by 75%, peroxidase activity by 31% while reducing malondialdehyde content by 34% in genotype Dessert indicating enhanced antioxidant defense and reduced oxidative damage. Likewise in genotype Royalty, stomatal conductance increased by 68%, with increasing specific area by 125% on melatonin treatment under severe water deprivation. The treatment also improved chlorophyll-a content by 93% in Royalty and 37% in Tyson, while decrease in malondialdehyde levels by 42% in Tyson, indicating reduced oxidative damage under severe water deprivation. In addition, melatonin increased photosystem II efficiency (Fv/Fm) in all genotypes with 27% increase in Royalty and improved quantum yield across all genotypes, regardless of the water deficit level. Conclusion Overall, melatonin treatment showed genotype-specific and dose-dependent effects in mitigating water deficit effects, offering a promising strategy to improve crop resilience and productivity in limited water environments. These results suggest the practical application for integrating melatonin treatments into sustainable agricultural practices, such as improving water deficit tolerance in sweet corn and potentially other crops, to maintain productivity under adverse climatic conditions.